Structural Changes of TiAl-Based Alloys during Mechanical Alloying - Bernatikova, Adriana; Novak, Pavel (Manufacturing Technology Journal, 2018)
Titanium aluminides represent a class of materials with unique mechanical and physical properties. This is reason why they are often used in aerospace or automotive industries. These materials form lamellar or nearly lamellar TiAl and Ti3Al phases. There are few methods how to synthesize Ti-Al based alloys, but they are often very difficult and expensive. In present work, a mechanical alloying which is probably best choice for synthesizing of Ti-Al intermetallic phases was used. Further, the most promising conditions of mechanical alloying allowing to create intermetallic phases were determined. It was shown, that by mechanical alloying allows to synthesize desired alloys with grains sizes of several tens of nanometres.
Keywords: titanium aluminides; structural changes; mechanical alloying